Analysis of the Role of Health Education in the Prevention of Dengue Fever in Remote Areas of Puskesmas Kota Padang Rejang Lebong Regency Bengkulu Province - Rustam Aji Rochmat; Abdul Kadir Hasan; Gustomo Yamistada; Wiwik Setyaningsih; Jessy Novita Sari; Sherly Ratih Frichesarius Santy Aji; Roro Ajhie Ayuningtyas; Wirawan Shakty; Agus Setya Budi (Miracle Journal Get Press, 2025)
Dengue fever (DHF) is a major public health problem in tropical regions, including Indonesia, due to high morbidity and environmental factors that support mosquito breeding. This study analyzed the role of health education in improving awareness and preventive behavior in remote communities under Puskesmas Kota Padang, Rejang Lebong Regency, Bengkulu Province. A one-group pretest-posttest design was applied to 90 purposively selected respondents. They were assessed before and after health education focusing on the 3M Plus method: draining, covering, recycling, and using larvicide. Results showed significant improvement in preventive behavior, with good practices increasing from 15.6% at pretest to 91.1% at posttest (p = 0.000). The findings indicate that health education effectively enhanced knowledge and promoted positive behavior toward dengue prevention. Continuous community involvement and government support are needed to sustain outcomes. Structured education programs are crucial to reducing dengue transmission, and further studies should explore long-term adherence and policy integration.